SISTEM KERJA HYBRID, WORK ENGAGEMENT, DAN KINERJA DOSEN: UNTUK PERLUASAN DAN PEMERATAAN AKSES PENDIDIKAN PERGURUAN TINGGI - Mokhammad Khukaim Barkhowa; Sephia Isyana Nabila (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
The decline in the number of students entering private universities has been recorded throughout Indonesia. There needs to be an expansion and equalization of access to higher education using a hybrid system. The purpose of this study is to examine how the hybrid work system and lecturer performance with the mediating role of work engagement on private university lecturers in Salatiga City. This scientific research was conducted on private university lecturers in Salatiga City based on the Central Statistics Agency of Salatiga City. Sampling in this study used calculations with the Slovin formula with a sample size of 86 lecturers. Sampling used simple random sampling. The data analysis tool to answer the research hypothesis used Smart Partial Least Square (PLS). The results of this study are that the hybrid work system has a positive effect on work engagement, the hybrid work system and work engagement have a positive effect on lecturer performance partially and work engagement functions as a mediator between the hybrid work system and lecturer performance. Private Universities in Salatiga City can pay attention to reporting on the hybrid work system, lecturers can enjoy the work completed in a hybrid manner and the lecturer's perseverance in completing work in a hybrid manner so that learning activities at Private Universities in Salatiga City can be maximized.